Systemic interferon alpha-2b increases the cure rate in laser treated patients with multiple persistent genital warts: a placebo-controlled study. Issue 2 (April 1991) - Petersen, C S; Bjerring, P; Larsen, J; Blaakaer, J; Hagdrup, H; From, E; Obergaard, L
Abstract : Systemic treatment modalities for eradication of multiple therapy resistant genital warts are so far not available. In this study laser treated patients with multiple genital warts received postoperatively either interferon alpha-2b subcutaneously (s.c.) 5 x 10(6) IU or matching placebo three times weekly for four weeks. At the conclusion of the study, 6-8 weeks after discontinuation of therapy, a significantly higher cure rate was found in the group of interferon-treated patients (14 of 27 (52%) patients cured) than among placebo treated patients (5 of 22 (23%) patients cured) (p less than 0.05). The side effects of fever, chills, myalgia, headache and leukopenia occurred more commonly in the interferon treated group than in the placebo group. However, only three of 32 patients discontinued interferon therapy because of side effects. We conclude that the addition of s.c. administered interferon alpha-2b to laser treated patients with chronic therapy resistant genital warts is fairly well tolerated and that it significantly enhances the chance of eliminating the disease.